Responsible pay: managing compliance, organizational efficiency and fairness in the choice of pay systems in China's automotive companies - Huang, Wei (International journal of human resource management, 2016)
This article explores the changing use of pay systems in China's automotive industry and contextual conditions shaping these changes: China's emerging market economy; and the evolution of collective labour relations. It sets out an integrated framework developed from institutional logics, new economics of personnel and organizational justice theory. The hypotheses derived from this framework are tested using the deductive case study method. The researcher collected the data in two waves of case studies including six Chinese automakers over 10 years. Key findings point to the convergence of pay strategy towards job values, performance and competence, and a wide variation in the use of variable pay and pay plan leverage. Through its exploration of forces underlying this convergence and variance in China's automotive industry, the article contributes to research on Strategic HRM and institutional complexity. The results highlight a variety of tensions among predictions of relevant theories. The outcome is subject to how employers interpret and manage institutional pluralism and complexity. The process by which employers choose response strategies also highlights the importance of responsible behaviours in choices of pay systems, which this article terms Responsible Pay.